DESAIN PENDIDIKAN AGAMA ISLAM DI PERGURUAN TINGGI UMUM BERBASIS EVOLUSI BUDAYA - Itah Miftahul Ulum (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2016)
Purpose of this study was to determine relationship of al-Quran and al-Sunnah with the rules offqh al-’ādatu muhakkamah and applicability in Islamic Religious Education (PAI) in Public HigherEducation (PTU), with no “scrape” exhausted culture or on the contrary, so intertwined harmonybetween Muslims and adherents of culture in society.Method used in study is content analysis, which is used to understand the rules of Arabic in verses ofthe Koran and Hadith of the Prophet of Islam and culture. In addition, also used discourse analysis,which is to connect the to the context as meaning implied relating to circumstances at time of verses ofKoran and Hadith of Prophet lowered.Results obtained from study of literature, that Islam gives the option to mankind to determine otheroptions, recognize and protect the right to life adherents of a different culture, and Islam is a universalreligion that has characteristics of al-wāqi’iyah (realistic), and can cooperate in preventing damage andbuild community.Keywords: Islamic religion and culture, al-’ādathu muhakkamah, Islamic Religious Education.